Study to Determine the Outcomes of Congenital Cataract Surgery - Khalil Khan Zahir, Shahid Anwar Bhatti, Muhammad Ayub Khan, Abdul Rafe, Haroon Saleem, Abdul Aziz, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aim of this study is to determine the outcomes of congenital cataract surgery. Place and Duration: Ophthalmology department of Hayatabad Medical complex Peshawar and Alshifa Trust Eye Hospital Rawalpindi for the duration from January 2022 to June 2022. Methods: A total of 200 eyes of 130 patients aged 3 to 8 with visually significant congenital cataracts (diameter ≥ 3 mm) were included in the interventional study. In all cases, posterior capsulotomy and anterior vitrectomy were performed. All patients were followed-up for six months. At follow-up; the patients’ surgical complications were managed along with treatment of amblyopia and visual acuity assessment was done. After six-months of follow-up; final outcome of congenital cataract surgery in relation of visual acuity was evaluated. Results: At the conclusion of the study, good vision was achieved in 52% of patients, and the better visual outcome was higher significantly in the younger age groups. The communal complication in our analysis was the fibrinous reaction. Conclusions: This study shows that early surgery for congenital cataract is beneficial and safe practice to obtain good visual acuity. Keywords: Congenital Cataract, Amblyopia, Visual Outcomes.